Impact of Grading on Quality Seedling Production in Swietenia macrophylla King - Patel, Nitin V. (Indian Forester, 2019)
An experiment was carried out to know the impact of grading on quality seedling production in Swietenia macrophylla King. The seeds (seed rate 1761 seeds kg-1) were collected from middle to mature age mother trees (15 to 18 years) from Arsikere Forest Range (Karnataka) were sowed in raised mother bed and from these 1374 seedlings were obtained with plant percent 78.02%. The 51 days old seedlings were graded in three grades G1 (> 21 cm), G2 (18 to 21 cm) and G3 (< 18 cm) based on seedling height. There were seven replications for each grade (treatment) and each replication contained 30 seedlings. The different growth parameters were recorded with two months interval until the six months growth of seedlings. The grade G1 remained superior to other grades in all recorded parameters. The outcome noticeably displayed that G1 recorded the highest biometric parameters viz., shoot length (50.53 cm), root length (40.23 cm), total plant length (90.76 cm), collar diameter (0.517 cm), number of leaflets (21.03), shoot dry weight (2.4706 g seedling-1), root dry weight (1.7804 g seedling-1), total dry matter production of plant (4.2510 g seedling-1), root/shoot ratio (0.7207) and quality traits like sturdiness quotient (9.79), quality index (0.3812) and volume index (13.55) at 180 DAT. Hence it is confirmed that seedling grading is worthy to produce quality planting stock for better success in out plantings as initially taller seedlings remain taller which may reduce rotation periods specially in fast growing species.